Antibiotic Prescribing in Connection to Childbirth: An Observational Study in Two Districts in Lao PDR - Weirong Yan; Anna Machowska; Amphoy Sihavong; Vanphanom Sychareun; Kongmany Chaleunvong; Bounxou Keohavong; Jaran Eriksen; Claudia Hanson; Manivanh Vongsouvath; Annelie Brauner; Mayfong Mayxay; Sengchanh Kounnavong; et al. (MDPI AG, 2022)
Overuse and misuse of antibiotics has frequently been reported for obstetric conditions and procedures, which may impact both the mother and the unborn baby and increase antibiotic resistance. This study aimed to investigate the antibiotic prescribing pattern in connection to childbirth in two districts in Lao PDR. It is a cross-sectional observational study. Antibiotic prescription data related to childbirth was collected via reviews of medical records in two district hospitals and five health centers in Lao PDR from September 2019 to November 2020. In total, antibiotic prescription data for 1777 women were extracted from their medical records. It was found that all women received antibiotics during in-patient care irrespective of delivery mode. When in hospital, 85.5% of the women who underwent a caesarean section got antibiotic treatment for 5 days and women who had a vaginal delivery usually had antibiotic treatment for one day or less. All the women got oral antibiotics for an additional 4-5 days upon discharge. Antibiotic prescription rate in connection to childbirth was very high in comparison with the WHO guidelines, and antibiotics were used extensively in the participating health facilities. Interventions to guide appropriate prescribing behavior in relation to childbirth are urgently needed in Lao PDR.